Islamic Psychology Approach Based on Edupreneurship Values in Increasing Student Learning Engagement in Islamic Religious Education (Case Study at MTs 2 Annuqayah Guluk-Guluk Sumenep 2026) - Suhairi Suhairi; Musleh Wahid; Muhtadi Abdul Mun’in (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the implementation of an Islamic psychology approach based on edupreneurship values by teachers in Islamic Religious Education (PAI) learning at MTs 2 Annuqayah Guluk-Guluk Sumenep. It also identifies the forms of student learning engagement (behavioral, emotional, and cognitive engagement) and the supporting and inhibiting factors. The focus is on the application of the Islamic psychology approach, the forms of student engagement, and the supporting and inhibiting factors. This study used a qualitative case study method. Data were collected through in-depth interviews with five key informants and 15 supporting informants, observations in two classes, grade VIII, and documentation conducted during December 2025. Data validity was maintained through triangulation of sources and techniques. The results indicate that the Islamic psychology approach based on edupreneurship is implemented as a holistic, integrative, and transformative learning approach. This approach successfully increased student learning engagement in Islamic Religious Education (PAI) learning at MTs 2 Annuqayah Guluk-Guluk.